Realisme versus Liberalisme: Suatu Perbandingan Paradigmatis - Mohamad Rosyidin (Indonesian Perspective, 2022)
Realism and liberalism are the most dominant paradigms in the study of International Relations. Both are often positioned diametrically because they have basic assumptions that contradict each other. Even though comparing the two paradigms violates the principle of incommensurability, it doesn't mean it's not useful. This paper attempts to map the two paradigms based on their underlying assumptions. Although in many respects realism and liberalism are opposites in viewing the phenomenon of international relations, both of them basically have similarities in viewing the nature of the international system and the nature of actors. This paper attempts to see what are the strong and weaknesses of each paradigm to see how far both are able to explain the phenomenon of international relations. Nevertheless, this paper does not pretend to judge one paradigm as better than another.